Regulation of the land castastre in the European Union: directions of adaptation for Ukraine - Martyn, A.; Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2018)
The guarantee of rights to land ownership and the formation of sustainable land use is one of the foundations of a stable and prosperous society, as well as the development of a market economy. In most European countries, land cadastral activities have long been separated into a different type of professional activity, which involves the preparation of secure and reliable information about land and other real estate, as well as their use. In many member states cadastral activities relate to qualified and duly licensed surveyors (land surveyors), surveyors or cadastral engineers. It is worth noting that the requirements for regulation of activities and recognition of professional qualifications of cadastral engineers differ significantly among European countries. The main activity of cadastral engineers in the real estate market is to provide state registration authorities with accurate and reliable data on real estate. Although this is the most common type of activity carried out by such engineers in Europe, historical, cultural, political, legal and other national peculiarities of countries have a significant influence on the conduct of this activity. The article analyzes the main features of land survey activity in the European Union member-states. In particular, the influence of state regulation on the conditions of work of land surveyors and their obligatory licensing is researched. The requirements of cadastral engineers for the possibility of work in the field of land management are shown, namely: relevant work experience, minimum education level, licensing conditions, etc. In addition, the types of responsibility for inadequate performance of cadastral activity and its results in European countries and Ukraine are analyzed. Comparison of land management practices in Ukraine and EU countries makes it possible to conclude that in our country borrowing of almost all forms of control by the state authorities of the market of the corresponding engineering services took place - from certification of performers to the exercise of state supervision. But the level of regulation and state intervention received in land management is clearly excessive and includes obvious corruption risks. Inspections of "quality of documentation" should not be repeated, and, instead, such verification should be carried out once at the stage of making information to the State Land Cadastre. In its turn, the only condition for access to the market for professional performers is to leave the existence of a professional liability insurance policy, because, unlike licensing or certification, only this mode of regulation can create real economic conditions for the reimbursement of losses caused by engineer errors. Keywords: European Union, geodetic works, land management, land surveyor, cadastre, licensing.